The correlation between length of surgery and the incidence of post anesthetic shivering and urinary retention in patients pasca spinal anesthesia - Suandika, Made; Susanto, Amin; Kurniawan, Hadi (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2024)
Abstract Background: Surgical procedures are inseparable from anesthesia, one of the anesthetic procedures is spinal anesthesia. Spinal anesthesia is the most common regional technique performed by most anesthesiologists worldwide. Spinal anesthesia is injecting local analgesic drugs into the subarachnoid space in the area between the lumbar vertebrae L2-L3 or L3 L4 or L4-L5. This study aims to determine the relationship between the duration of surgery and the occurrence of Post Anesthetic Shivering and urinary retention in patients after spinal anesthesia in the recovery room of RSU Aisyiyah Padang. Method: This research method is descriptive quantitative with a cross-sectional approach. The sampling technique used no random sampling with a total sampling of 30 respondents. Data was taken using demographic data for gender and age data. Results: Respondents with the most dominant age category were adults aged 26-45 years, namely 17 respondents (56.7%). Respondents with a more dominant Gender category, namely Women, were 18 respondents (60.0%). In the category of length of surgery, namely more than >1-2 hours, namely 20 respondents (66.7). Based on the category of shivering frequency, the most dominant one is not shivering, as many as 16 people (53.3). The incidence of urine retention, most respondents did not experience urine retention, as many as 27 respondents or (90.0). Conclusion: There is no relationship between the length of surgery and the incidence of post-anesthetic shivering (pas) and urine retention and the direction of the relationship is positive.